2018
DOI: 10.3390/md16050159
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes from the Marine Algae of the Genus Dictyota

Abstract: Species of the brown algae of the genus Dictyota are rich sources of bioactive secondary metabolites with diverse structural features. Excellent progress has been made in the discovery of diterpenes possessing broad chemical defensive activities from this genus. Most of these diterpenes exhibit significant biological activities, such as antiviral, cytotoxic and chemical defensive activities. In the present review, we summarized diterpenes isolated from the brown algae of the genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 92 publications
(190 reference statements)
2
47
0
Order By: Relevance
“…Up to the present time, 9 spatane diterpenes have been found in D. marginatus or D. okamurai ( Figure 3; Table 2). Five spatane compounds (20)(21)(22)(23)(24) are isolated from the brown alga D. marginatus collected from Collaroy, New South Wales, Australia. 8 Compounds 21 and 22 are also isolated from the brown alga D. okamurai collected on the coast of Kamaishi, Iwate Prefecture, Japan.…”
Section: Spatane Diterpenesmentioning
confidence: 99%
“…Up to the present time, 9 spatane diterpenes have been found in D. marginatus or D. okamurai ( Figure 3; Table 2). Five spatane compounds (20)(21)(22)(23)(24) are isolated from the brown alga D. marginatus collected from Collaroy, New South Wales, Australia. 8 Compounds 21 and 22 are also isolated from the brown alga D. okamurai collected on the coast of Kamaishi, Iwate Prefecture, Japan.…”
Section: Spatane Diterpenesmentioning
confidence: 99%
“…Group II involves the same cyclization of gernayl-geraniol pre-cursor but between C-1 and C-11, while Group III involves cyclization between C-2 and C-10. Diterpenes of all three groups are reported to exhibit significant anti-tumor, anti-viral and some anti-fouling activities [73]. A distribution of the diterpene compounds reported in this review by species and locality is shown in Table 6.…”
Section: Sesquiterpenes and Monoterpenesmentioning
confidence: 95%
“…The diterpenes (C-20) from brown algae have been extensively studied and reviewed, and none more so than the diterpenes derived from algae within the genus Dictyota [73]. The Dictyota genus is within the family Dictyotaceae and consists of some 221 species.…”
Section: Sesquiterpenes and Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…This weed is also rich in phytochemical constituents such as flavonoids, tannins, phenolics, sterols and terpenoids that activate defense mechanism against different infectious diseases 3 . Dictyota dichotoma (brown algae), belonging to the family Dictyotaceae, has medicinal implications for its secondary metabolite content with antithrombolytic, antifouling, anti-tumor, antibacterial and antifungal properties 4 . Caulerpa peltata (green algae), belonging to the family Caulerpaceae, is traditionally used for its antibacterial, antiproliferative, and immuno-stimulatory properties 5 .…”
mentioning
confidence: 99%